PENGARUH KARAKTERISTIK INDIVIDU, KOMPETENSI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PENYULUHAN KELUARGA BERENCANA KABUPATEN MAMUJU PROVINSI SULAWESI BARAT - Rusmiah Rusmiah; Nurdin Brasit; Ria Mardiana (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
Family planning extension officers (PKB) is an asset of human resources that will determine the success of the management of the programme at the level of field lines KB. This research aims to find out and analyze between individual characteristics, competencies, and an influential work environment more dominant performance against the extension officers KKBPK Mamuju Regency. The design of the research uses descriptive analistis approach (analytical descriptive approach) quantitatively. The population in this research is the extension officers KKBPK-KB Office of population and Control KB Mamuju Regency totaled 40 people extension officers of KKBPK. The samples will be used in this research is 40 power extension officers KB Mamuju Regency. The technique of data collection is done using interviews, observation, Questionnaire, and documentation. The results showed that individual Characteristics, competencies, and simultaneously working environment positive and significant effect on performance extension officers KB in Mamuju Regency. Competence is more dominant in affecting the performance of extension officers KB in Mamuju Regency with the value of the component's largest beta 0567. While the individual karasteristik and the respective working environment of 0.253 and 0.196.